Perancangan Karakter Animasi Calon Arang Untuk Youtube HNS Studio - Wahyudi, I Kadek Wahyudi Putra; Bayu Artha, I Gede Agus Indram; Kharismawan, Putu Gede Satria (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
The role of animated characters is part of the animation creation process, where character design plays an important role in depicting each character contained in an animation later. This project discusses the design of the animated character Calon Arang for HNS Studio YouTube, where the designer starts from the brainstorming, sketching, contouring and coloring process. There are several methods used in this design, namely the participation method, observation method and documentation method. The results of this approach produce characters such as Calon Arang, Ratna Manggali, Mpu Baradah, Mpu Bahula, Raja Erlangga, Patih, Sisya and the character of an assassin, of course adding aspects of innovation but still steeped in tradition.